Effects and moderators of exercise on quality of life and physical function in patients with cancer: An individual patient data meta-analysis of 34 RCTs. (January 2017) - Buffart, Laurien M.; Kalter, Joeri; Sweegers, Maike G.; Courneya, Kerry S.; Newton, Robert U.; Aaronson, Neil K.; Jacobsen, Paul B.; May, Anne M.; Galvão, Daniel A.; Chinapaw, Mai J.; Steindorf, Karen; Irwin, Melinda L.; et al.
Highlights: This meta-analysis of individual patient data from 34 randomised controlled trials ( n = 4519 patients) found significant benefits of exercise effects on quality of life and physical function. Exercise effects on quality of life and physical function were comparable across patients with different demographic and clinical characteristics. Exercise effects on quality of life and physical function were significantly larger for supervised than unsupervised interventions. Abstract: This individual patient data meta-analysis aimed to evaluate the effects of exercise on quality of life (QoL) and physical function (PF) in patients with cancer, and to identify moderator effects of demographic (age, sex, marital status, education), clinical (body mass index, cancer type, presence of metastasis), intervention-related (intervention timing, delivery mode and duration, and type of control group), and exercise-related (exercise frequency, intensity, type, time) characteristics. Relevant published and unpublished studies were identified in September 2012 via PubMed, EMBASE, PsycINFO, and CINAHL, reference checking and personal communications. Principle investigators of all 69 eligible trials were requested to share IPD from their study. IPD from 34 randomised controlled trials ( n = 4519 patients) that evaluated the effects of exercise compared to a usual care, wait-list or attention control group on QoL and PF in adult patients with cancer were retrieved and pooled. Linear mixed-effect models were used to evaluate the effects of the exercise on post-intervention outcome values ( z -score) adjusting for baseline values. Moderator effects were studies by testing interactions. Exercise significantly improved QoL ( β = 0.15, 95%CI = 0.10;0.20) and PF ( β = 0.18, 95%CI = 0.13;0.23). The effects were not moderated by demographic, clinical or exercise characteristics. Effects on QoL ( β difference_in_effect = 0.13, 95%CI = 0.03;0.22) and PF ( β difference_in_effect = 0.10, 95%CI = 0.01;0.20) were significantly larger for supervised than unsupervised interventions. In conclusion, exercise, and particularly supervised exercise, effectively improves QoL and PF in patients with cancer with different demographic and clinical characteristics during and following treatment. Although effect sizes are small, there is consistent empirical evidence to support implementation of exercise as part of cancer care.